A Comparison of Stryker Xia3 and Depuy Expedium FAS Instrumentation for the Correction of Adolescent Idiopathic Scoliosis. Issue 1 (April 2016) - Khan, Almas; Fragakis, Angelo; Loughenbury, Peter; Ong, Jeffrey; Husein, Rodwan
Introduction: In 2012, our institution held a tender for the supply of its instrumentation which resulted in a majority supply being awarded to Stryker for Xia3 spinal instrumentation. Prior to this we had been using Depuy Expedium FAS for the preceding 5 years. As the surgeons would have to go through a learning curve for the use of the instrumentation system, we felt it important to demonstrate that the correction of curve obtained and the intraoperative risks were the same for each from the outset of the change. Material and Methods: We examined the post-operative X-rays of our patients who had adolescent idiopathic scoliosis corrected in our institution using Expedium FAS and Xia3 instrumentation between 2011 and 2014. We excluded curves that had previously had growing rods, previous pseudarthrosis or other spinal complication, anterior spinal surgery, implant removal, and incomplete records. Patients were identified using our hospital's theater management software. We measured the pre- and postoperative and 1 year follow up Cobb angle on our PACS system. Blood loss and transfusion requirements were obtained from our cell-saver and blood bank database, and other information was obtained from the clinical notes. Results: 173 patients were identified. 53 had incomplete datasets. 22 were excluded due to having previous growing rod, combined anterior/posterior procedure, or a Skagg's Procedure. 63 cases using Expedium FAS and 35 of Xia3 were found. Expedium had 59 (21–99)% curve correction, 5.40 (2–12.5) hours operative time, 0.87 (0.2–1.5)l intraoperative blood loss and 8.5 (5–42) days hospital stay. The Xia3 group had 63 (34–90) % curve correction, 4.87 (3–7.5) hours operative time, 1.6L (0.4–2.5)l blood loss, and 10 (5–42) days LOS. Only the difference in blood loss reached statistical significance, however transfusion rates were the same. Conclusion: Despite being at different parts of the learning curves with each instrumentation systems, a group of 4 experienced scoliosis surgeons were able to achieve equal correction of scoliosis using either instrumentation systems in all variables except for blood loss. Moving instrumentation systems can be daunting, however can be done safely if managed in a proactive manner.